DISTANCE LEARNING METHODS FOR STEM EDUCATION COURSES - Bostanov, Б.Г; Grigoriev, С.Г; Nurlybaev, K.K (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
New technologies and innovative devices are increasingly penetrating into human life, actualizing the need for their development and implementation. An important role in this process is the training of teachers who are able to master and use such equipment in the field of education. Currently, STEM education is becoming increasingly popular, allowing you to quickly master new devices and technologies. Special pedagogical STEM parks are being created, where innovative techniques are being tested in the training of teachers. In Kazakhstan, as well as other countries with vast territories, the development of STEM education is possible through the use of remote forms of organization of the educational process. This paper discusses possible ways to use and develop distance-learning forms in the organization of STEM courses. Models of organizing courses on mechatronics and robotics based on the use of new educational devices are proposed.